Artificial Intelligence Techniques Application in UAS - Zosimovych, Nickolay (Transactions on Engineering and Computing Sciences, 2023)
This paper depicts the progress of an appliance of Artificial Intelligence (AI) for Unmanned Aerial System (UAS) control. This job was done as part of the conditions for lectures and labs in AI at the School of Robotics, and a beginning project platform for research projects at Xi’an Jiaotong-Liverpool University for a flexible, healthy, and intelligent unmanned aerial vehicle (UAV) mission control system. A method is outlined which allows a base level application for applying an artificial intelligence method, fuzzy logic, to aspects of control logic for UAV flight. The benefits of using fuzzy logic for a movement planner were shown in this research: a small number of failures, near-optimal pathways, and low control attempts. It is these benefits that make it a nice tool for additional improvement. Some elements of UAV flight, automated direction, altitude is held, and prevention of dynamic obstacles, have been implemented and results analysis displayed. Certain potential clear future works that were not investigated in this study are motion-planning in three dimensions, prevention of dynamic obstacles, and more robust analysis.